PERAN NIRMANA TRIMATRA DALAM PROSES STUDI PERANCANGAN DESAIN INTERIOR THE PURPOSE OF NIRMANA TRIMATRA IN INTERIOR DESIGN STUDY PROCESS - Merati, Made Widyatantri (Universitas Gunadarma, 2025)
Design education, especially interior design, as a branch of applied creativity is education with various disciplines which, as time goes by, often experiences changes and challenges phenomenon. Various methods and variation of ‘creating’ techniques are used to produce design works that are innovative, creative, have a ‘noble’ meaning, and are well designed. Nirmana trimatra as basic visual education, is one of the design activities or methods in the design process, in order to produce design work that is full of aesthetics and useful values. This writing aims to discuss the nirmana trimatra study process carried out by interior design students in Depok and the importance of this process in designing interior designs. Through this writing, in essence, nirmana trimatra abilities which are closely related to sensivity to visual design composition and spatial intelligence are very important for the field of interior design, and the development of basic education must always be intensified and improved.